Cross-Canada Survey of Resistance of 2747 Aerobic Blood Culture Isolates to Piperacillin/Tazobactam and Other Antibiotics. (1998) - Forward, Kevin R; Franks, Patricia A; Low, Donald E; Rennie, Robert; Simor, Andrew E; the Canadian Piperacillin/Tazobactam Study Group,
Abstract : OBJECTIVE: To compare the activity of piperacillin/tazobactam with that of other broad parenteral antibiotics against aerobic and facultative anaerobic blood culture isolates in a Canada-wide survey. DESIGN: Fifty-eight laboratories in nine provinces each contributed up to 50 consecutive clinically significant aerobic and facultative anaerobic isolates for susceptibility testing. SETTING: Participating hospitals included both tertiary care and community hospitals. MATERIALS AND METHODS: Testing was performed in five regional centres by using the same microbroth dilution method, and results were interpreted according to National Commitee for Clinical Laboratory Standards M7-A3 and M100-S5 guidelines. RESULTS: Piperacillin/tazobactam and imipenem were both active against more than 99% of the 1616 strains of Enterobacteriaceae species tested. The minimum inhibitory concentration of 90% of isolates (MIC90 ) of all Enterobacteriaceae species was 2 mg/L for piperacillin/tazobactam compared with 64 mg/L for piperacillin alone. Seventeen per cent of strains of Enterobacteriaceae species were susceptible to piperacillin/tazobactam but resistant to piperacillin. Piperacillin/tazobactam was highly active against Pseudomonas aeruginosa, inhibiting 99.1% of strains. MIC90 was 8 mg/L. Nine per cent of P aeruginosa strains were not susceptible to imipenem. Most of these strains had a MIC of 8 mg/L, which falls in the intermediate category. Ninety-seven per cent of P aeruginosa were susceptible to ciprofloxacin and 97.3% to tobramycin. Ninety-six per cent of strains of Actinobacter species were susceptible to piperacillin/tazobactam, whereas only 76% of strains were susceptible to piperacillin alone. Overall, piperacillin/tazobactam was the most active agent tested; 98% of all strains were susceptible, followed closely by imipenem, to which 97.8% of strains were susceptible. CONCLUSIONS: Aerobic blood culture isolates from Canadian centres continue to be highly susceptible to a variety of antibiotics. The broad spectrum of activity of piperacillin/tazobactam suggests that this combination should be considered for empirical treatment of sepsis while awaiting results of cultures and susceptibility testing.